Adoption of collaboration information technologies in Australian and US organizations: a comparative study - Bajwa, D.; Lewis, L.; Pervan, Graham (IEEE Computer Society, 2003)
Collaboration to accomplish tasks has taken on a new meaning over the past few years. The majority of organizations are viewing information technology (IT) as a key enabler to transcend time and distance barriers to collaborate efficiently and effectively. Despite this, we know very little about the macro level adoption of IT to support collaboration. This paper assesses the pattern of adoption of seven IT clusters to support task-oriented collaboration in US and Australian organizations. Data collected from one hundred and forty Australian organizations and one hundred and nineteen US organizations is analyzed to compare adoption patterns. Our results suggest that stand-alone e-mail systems, audio teleconferencing systems, and videoconferencing are the most widely adopted technologies to support collaboration in both countries while web-based tools and electronic meeting systems are the least commonly adopted. A further analysis of data suggests that promotion of collaboration, mode of collaboration, and the adoption of some IT clusters are affected by region. Implications of these findings are discussed along with some directions for practice and research.